Preventing rare contralateral ureteral injury during robotic-assisted nephroureterectomy: lessons from a surgical complication - Yen Ho; Chung-Howe Lai; Kuan-Ting Lin; Ke-Hsun Lin; Syuan-Hao Syu (BMC Urology, 2025)
Abstract Robotic-assisted laparoscopic nephroureterectomy (RALN) is a common approach for upper tract urothelial carcinoma (UTUC), offering advantages such as reduced morbidity and improved recovery. However, contralateral ureteral injury during bladder cuff excision is extremely rare and can be challenging to manage. We present the case of a 56-year-old male with low-grade urothelial carcinoma of the right renal pelvis who underwent RALN. Anatomical distortion during surgery led to misplacement of a surgical clip at the contralateral ureterovesical junction, resulting in obstruction and anuria. Urgent cystoscopy and ureteroneocystostomy with stent placement successfully restored ureteral function. This case highlights the importance of thorough preoperative planning, careful anatomical verification, and heightened intraoperative vigilance to prevent such rare complications in robotic surgery. Ensuring accurate identification of anatomical structures is crucial to avoid inadvertent injury, specifically in complex urologic oncology procedures.